Comparison of brain gray matter volume changes in peritoneal dialysis and hemodialysis patients with chronic kidney disease: a VBM study - Xiao, Fenglin; Zhou, Lili; Li, Yan; Zhang, Chaoyang; Liu, Ying; Yu, Huan; Li, Xiaoping; Wang, Chunyu; Yin, Xinxin; Gao, Xin (Frontiers in Neuroscience, 2024)
To compare gray matter volume changes in patients with chronic kidney disease (CKD) undergoing peritoneal dialysis (PD) and hemodialysis (HD) using voxel-based morphometry (VBM).: 27 PD patients, 25 HD patients, and 42 healthy controls were included. VBM analysis was performed, and cognitive function was assessed using the Simple Mental Scale of Intelligence (MMSE) and the Montreal Cognitive Assessment Scale (MoCA). Correlation between cognitive function and changes in brain gray matter volume was analyzed. RESULTS: Both peritoneal dialysis and hemodialysis patients had partial gray matter volume reduction compared to controls, but the affected brain regions were not uniform. hemodialysis patients had greater volume reduction in certain brain regions compared to PD. MMSE and MoCA scores were positively correlated with gray matter volume changes. CONCLUSIONS: Different dialysis modalities cause damage to specific areas of the brain, which can be detected using VBM. VBM combined with cognitive function assessment can help detect structural brain changes and cognitive impairment in patients with different dialysis modalities. The comprehensive application of VBM in the field of neurological function deserves further exploration.